Pengaruh Pemberian Motivasi Belajar dan Efektivitas Pembelajaran Mata Pelajaran PAK Terhadap Prestasi Belajar Siswa SMP Negeri di Kota Manado - Tampung, Widya; Kambey, Ellen; Lagun Siang, Jhoni (Peneliti.net, 2024)
This research aims to determine the effect of providing learning motivation and the effectiveness of learning PAK subjects on the learning achievement of State Middle School students in Manado City. This research uses a quantitative approach with a survey research method whose design is associative descriptive. The sampling technique used is probability sampling with purposive sampling technique. The findings of this research show that there is an influence of the learning motivation variable (X1) on the learning achievement variable (Y). This is based on the results of the t test (partial) which states that the t-count value is 4,156 ≥ 2,048 (t-table value). This shows that there is an influence based on the results of the t test. It is also known that the significance value is 0.001 ≤ 0.05. Other test results also show that there is the influence of the learning effectiveness variable in PAK subjects (X2) on the learning achievement variable (Y). This is based on the results of the t test (partial) which states that the calculated t-value is 3,726 ≥ 2,048 as large as(t-table value). This shows that there is an influence based on the results of the t test. It is also known that the significance value is 0.001 ≤ 0.05. Other findings also state that based on the f test, it can be seen that the calculated f value is 39,393 ≥ 3.30 (F-table value), which means that there is an influence. Based on the results of the F test above, it is also known that the significance value is 0.001 ≤ 0.05, meaning, H0 is rejected and H1 is accepted, so it can be concluded that the variables providing learning motivation (X1) and learning effectiveness (X2) together have a significant effect on the learning achievement variable. (Y). This is also from the results of the coefficient of determination which shows that R square (R2) has a value of 0.738 or 73.8%. So it can be concluded that the magnitude of the influence of the variables providing learning motivation and learning effectiveness on student learning achievement is 0.738 (73.8%).